2012
DOI: 10.1021/jf204420x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antityrosinase Mechanism of Benzaldehyde Thiosemicarbazones: Novel Tyrosinase Inhibitors

Abstract: p-Hydroxybenzaldehyde thiosemicarbazone (HBT) and p-methoxybenzaldehyde thiosemicarbazone (MBT) were synthesized and established by (1)H NMR and mass spectra. Both compounds were evaluated for their inhibition activities on mushroom tyrosinase and free-cell tyrosinase and melanoma production from B(16) mouse melanoma cells. Results showed that both compounds exhibited significant inhibitory effects on the enzyme activities. HBT and MBT decreased the steady state of the monophenolase activity sharply, and the I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 24 publications
4
37
3
Order By: Relevance
“…4c), which all passed through the origin. This result is similar to that reported by Chen et al (2012). An increase of inhibitor concentration resulted in decrease of the slope of the line, indicating that the presence of inhibitor did not reduce the quantity of enzyme, but just resulted in the inhibition of enzyme activity.…”
Section: Inhibition Mechanismsupporting
confidence: 91%
See 1 more Smart Citation
“…4c), which all passed through the origin. This result is similar to that reported by Chen et al (2012). An increase of inhibitor concentration resulted in decrease of the slope of the line, indicating that the presence of inhibitor did not reduce the quantity of enzyme, but just resulted in the inhibition of enzyme activity.…”
Section: Inhibition Mechanismsupporting
confidence: 91%
“…3b (curve II). Similar results were obtained in the investigation of mushroom tyrosinase inhibition by other inhibitors, such as p-methoxybenzaldehyde thiosemicarbazone (MBT) and some alpha-substituted derivatives of cinnamaldehyde (Chen et al 2012;Cui et al 2015). The increase in lag time indicates an inhibition of monophenolase activity, which subsequently led to a reduction in total tyrosinase activity (Anish and Adinpunya 2014).…”
Section: Inhibitory Effect Of Compound 1 On Monophenolase Activity Ofsupporting
confidence: 67%
“…Furthermore, we found that C-9 has two different inhibitory mechanisms within two concentration ranges. That was quite different from other tyrosinase inhibitors we previously studied [23][24][25]. We also found that C-9 had stronger bacteriostatic activity than previously identified compounds [26].…”
Section: Introductioncontrasting
confidence: 99%
“…The characteristic maximum at 276.5 nm of compound oxygen of tyrosinase, which weakened the role of tyrosinase (Chen et al, 2012). Therefore, free radical scavenging compounds could also be used as a cosmetic ingredient to relieve skin aging (Tanaka et al, 2004).…”
Section: Methodsmentioning
confidence: 99%